Use of Submicron Vaterite Particles Serves as an Effective Delivery Vehicle to the Respiratory Portion of the Lung; Frontiers in Pharmacology; Vol. 9 - Guslyakova O. I. Olga Igorevna; Atochina E. N. Elena Nikolaevna; Sindeeva O. A. Olga Aleksandrovna; Sindeev S. S. Sergey Sergeevich; Pinyaev S. I. Sergey Ivanovich; Pyataev N. V. Nikolay Vasiljevich; Revin V. V. Viktor Vasiljevich; Sukhorukov G. B. Gleb Borisovich; Gorin D. A. Dmitry Aleksandrovich; Gow A. J. Andrew John (2018, 2018)
Title screen